Effectiveness of Tutorial Videos in Enhancing Pronunciation: A Study on Cambodian EFL Learners and Social Implications - Hak Chamroeun (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The research aimed to examine how well tutorial videos could aid in developing the pronunciation skills of Cambodian EFL learners and to explore their perceptions of this learning method. Methodology: Data collection employed both quantitative (pre-test and post-test) and qualitative (semi-structure interview) were used to figure out the significant difference between both groups and learners perceptions toward the use of tutorial video in enhancing pronunciation. Main Finding: The findings indicate that using technology-based teaching approach—tutorial videos effectively enhance pronunciation for Cambodian EFL learners between different socio-economic backgrounds, with private students achieving greater improvement due to the early exposure and technology accessibility. Moreover, despite minor challenges, learners find learning pronunciation through tutorial videos enjoyable, motivating, and beneficial in reducing speaking anxiety through repeated practices. The study also demonstrates its social implications of technology in language learning, as it can close the socio-economic gaps by providing equal learning opportunities, making them more competitive in the job market and for future academic success. It emphasizes the important for instructor of integrating technology in pronunciation, as it is equally important as other language skills. Novelty/Originality of this study: This study is original as no prior research at the researcher’s organization, National University of Battambang (NUBB). It mainly focusses on the effectiveness of tutorial videos on learners’ pronunciation from two different context—public and private schools which allows to explore the benefits of tutorial videos on English pronunciation development as well as fulfill the research gap at the institution.